Risk factors for prolonged viral RNA shedding in patients with COVID-19; a nested case-control study - Yasemin Nadir; Pinar Kiran (Journal of Infection in Developing Countries)
Introduction: The coronavirus disease 2019 (COVID-19) pandemic continues to have a global impact. The behavior and viral course of severe acute respiratory syndrome coronavirus (SARS-CoV-2) remains unpredictable. We aimed to investigate the prediction factors associated with prolonged viral shedding in COVID-19 patients.